2019
DOI: 10.1016/j.socec.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Time pressure and risk taking in auctions: A field experiment

Abstract: Auctions often require risk taking under time pressure. However, little is known about how time pressure moderates the relationship between uncertainty of outcomes and bidding behavior. This study consists of a field experiment in which participants are invited to a Vickrey auction to elicit their willingness to pay for a lottery ticket. The time available to place a bid and also the skewness of the lottery (holding the expected value constant) are systematically manipulated. We find that under high time press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Time pressure has also been shown to increase participants' preferences for a known payoff over an uncertain alternative in the domain of gains 45 , although the inverse was true in the domain of losses. There are also similar findings from description-based gambles, where time pressure can increase risk aversion in the domain of gains 46 , with field experiments also showing that time pressure decreases risk-taking in auctions 47 .…”
Section: Limiting Decision Timesupporting
confidence: 66%
“…Time pressure has also been shown to increase participants' preferences for a known payoff over an uncertain alternative in the domain of gains 45 , although the inverse was true in the domain of losses. There are also similar findings from description-based gambles, where time pressure can increase risk aversion in the domain of gains 46 , with field experiments also showing that time pressure decreases risk-taking in auctions 47 .…”
Section: Limiting Decision Timesupporting
confidence: 66%
“…For example, consumers are more likely to choose a retailer with smaller but more consistent discounts (higher probability, lower discount) over a deeper discounting, yet more unpredictable retailer (lower probability, higher discount;Danziger et al, 2014). Furthermore, this pattern of risk aversion tends to be even stronger when monetary gambles involve higher payoffs or stakes (e.g., hundreds vs. tens of dollars), real incentives versus hypothetical choices (Fehr-Duda, Bruhin, Epper, & Schubert, 2010;Holt & Laury, 2002;Kachelmeier & Shehata, 1992), or time pressure (El Haji, Krawczyk, Sylwestrzak, & Zawojska, 2016).…”
Section: Decision Making Under Riskmentioning
confidence: 99%
“…In contrast, those under the risk frame made safer decisions under time pressure than participants under the risk frame that were not under time pressure. These results indicate that, rather than participants becoming globally more risk seeking (Chandler & Pronin, 2012;Madan et al, 2015) or risk avoidant (Ben Zur & Breznitz, 1981;El Haji et al, 2016), there was a reversal in risk preference, as was found by Saqib and Chan (2015). Because the methodology between the current study and that by Saqib and Chan are vastly different, it is not possible to directly compare the reversal in risk preference; that said, the reversal of risk preference under time pressure in the current study lends credence to the notion that the prospect theory's (Tversky & Kahneman, 1981) S-curve inverts.…”
Section: Discussionmentioning
confidence: 83%
“…There are findings that suggest that risk taking decreases under time pressure (Ben Zur & Breznitz, 1981;El Haji, Krawczyk, Sylwestrzak, & Zawojska, 2016) and those that suggest the opposite (Chandler & Pronin, 2012;Madan, Spetch, & Ludvig, 2015). As a result, further research is needed to understand the influence of time pressure for decisions made under gain and loss frames.…”
mentioning
confidence: 99%